Unlocking the potential of antimicrobial peptides: Beta-defensins and the future of cancer diagnostics - Saranya Velmurugan; Gowtham Kumar Subbaraj (Oral Oncology Reports)
Oral cancer is a significant public health concern globally, with India reporting a high incidence rate. Genetic factors related to immunity, taste perception, and tooth mineralization are being increasingly studied in the context of dental caries. Beta-defensins, a group of antimicrobial peptides crucial for innate immunity, have been linked to oral cancer development. Studies have shown dysregulation of beta-defensins, particularly hBD-3, may contribute to oral squamous cell carcinoma progression via modulation of inflammation and immune responses. The Beta-defensin index (BDI), which measures hBD-3 and hBD-2 ratios, shows promise as a non-invasive test for early oral cancer detection. Clinical applications include guiding biopsy decisions and prognostication. Further research on beta defensins’ mechanisms and broader oncological implications is crucial for innovative therapeutic strategies.